2018
DOI: 10.1164/rccm.201707-1368oc
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Airway Submucosal Glands and TP63+KRT5+ Basal Cells in Obliterative Bronchiolitis

Abstract: SMGs and basal SC compartments are depleted in large and/or small airways of lung allografts, and basal SC proliferative capacity declines with progression of disease and phenotypic changes. Global airway SC depletion may be a mechanism for pulmonary allograft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 43 publications
8
42
0
Order By: Relevance
“…While lung transplantation does provide an excellent quality of life, unfortunately, a majority of lung-transplant recipients develop obliterative bronchiolitis (OB) within 5 years of transplantation, significantly reducing the long-term survival prospects of these patients (2). The reasons why lung-transplant recipients develop OB is not entirely understood, but it is believed to result in part from injury-induced exhaustion of airway epithelial stem cells (3)(4)(5). Our recent findings confirm that as chronic lung allograft disease pathology worsens somatic lung stem cells diminish from both small and large airways and submucosal glands (SMGs) (5).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…While lung transplantation does provide an excellent quality of life, unfortunately, a majority of lung-transplant recipients develop obliterative bronchiolitis (OB) within 5 years of transplantation, significantly reducing the long-term survival prospects of these patients (2). The reasons why lung-transplant recipients develop OB is not entirely understood, but it is believed to result in part from injury-induced exhaustion of airway epithelial stem cells (3)(4)(5). Our recent findings confirm that as chronic lung allograft disease pathology worsens somatic lung stem cells diminish from both small and large airways and submucosal glands (SMGs) (5).…”
supporting
confidence: 68%
“…The reasons why lung-transplant recipients develop OB is not entirely understood, but it is believed to result in part from injury-induced exhaustion of airway epithelial stem cells (3)(4)(5). Our recent findings confirm that as chronic lung allograft disease pathology worsens somatic lung stem cells diminish from both small and large airways and submucosal glands (SMGs) (5). Understanding the mechanisms that contribute to stem cell depletion will enable further interventions aimed at treating and/or preventing OB.…”
supporting
confidence: 57%
“…The mechanisms driving stem cell depletion remain a major challenge in the field. Using a ferret model of OB, P arekh and co-workers [ 84 ] (University of Iowa, USA) demonstrated that both small and large airways are affected in OB, a disease previously believed to affect only distal airways. Upon OB development, basal epithelial cells are diminished from small and large airways and submucosal glands.…”
Section: Session IX New Strategies For Cellular Delivery and Regenermentioning
confidence: 99%
“…However, the lung parenchyma is surprisingly spared in transplant-associated OB, arguing against a generalized allotypic response and perhaps a more specific response to the very cells responsible for the regenerative maintenance of the small airways. Swatek et al (5) couple lung transplants between outbred ferrets known to yield an OB indistinguishable from that seen in human recipients with stem cell clonogenic analyses to reveal an altogether new facet of OB pathobiology. While their key findings that p63+/Krt5+ stem cells are progressively depleted from both small and large airways as well as destruction of submucosal glands (SMG) during lung rejection are detailed in the excellent editorial by Smirnova and Eickelberg (6), here we will focus some of the broader implications of Swatek et al as they pertain to our limited understanding of airway stem cells, the potential of stem cell cloning to fill these gaps, and the very real possibility that such epithelial airway stem cells will form the basis of autologous solutions to the problem of chronic lung disease.…”
mentioning
confidence: 99%
“…Importantly, these three types of p63+/Krt5+ airway stem cells are epigenetically fixated on those fates for upper or lower airway epithelia regardless of how long they have been propagated in vitro as single cell-derived clones, and do not get confused or show obvious plasticity in these respective fates. As revealed by Swatek et al (5), the above scheme does not factor in the consequences of losing the p63+/Krt5+ basal stem cells precursors of the SMGs in OB, as their relative fate properties have not been worked out at the clonal level. This gap in accommodating SMG p63+/Krt5+ stem cells in airway regenerative properties underscores what is likely an enormous gap in our understanding of stem cells of the airways in general.…”
mentioning
confidence: 99%